Hysteresis in unemployment in Slovakia - Řeháková, Magdaléna (2019)
In this thesis I present the theoretical background for the study of hysteresis in unemployment and its various potential sources and mechanisms through which hysteresis works with emphasis on the Slovak labor market context. I provide a review of available literature on hysteresis concerning Slovakia and regional analysis of this topic. I study the presence of hysteresis in Slovak unemployment rates at the country level as well as at the regional level. At the country level I use the unit root test with two endogenously determined breaks. Regions are being analyzed by univariate unit root tests and by the second-generation panel unit root tests. I cannot reject the hysteresis hypothesis neither at country-wide nor at the regional level. In the end, I present a discussion on policy implications.